Improved Random Area Selective Image Steganography with LSBMR - Abraham, Neethan Elizabeth; Chandran, Reshm; Jyothisree; Thomas, Sunu Ann (International Journal of Computer Sciences and Engineering, 2025)
Image steganography is the art of hiding secret message in grayscale or color images. Easy detection of secret message for any state-of-art image steganogra- phy can break the stego system. To prevent the breakdown of the stego system data is embedded in the selected area of an image which reduces the probability of detection. Most of the existing adaptive image steganography techniques achieve low embedding capacity. In this paper a high capacity Predictive Edge Adaptive image steganography technique is proposed where selective area of cover image is predicted using Modified Median Edge Detector (MMED) predictor to embed the binary payload (data). The cover image used to embed the payload is a grayscale image. Experimental results show that the proposed scheme achieves better embedding capacity with minimum level of distortion and higher level of security. The proposed scheme is compared with the existing image steganography schemes. Results show that the proposed scheme achieves better embedding rate with lower level of distortion.